The Crucial Role of Indonesian CEOs in Tax Decision-Making: An Examination of Tax Avoidance Practices - Sahrian Aditya Rahmatulloh; Dwi Ladyssa Nainggolan (Journal of Applied Accounting and Taxation, 2024)
This study aims to fill a research gap by exploring how Indonesian CEOs' demographic traits and management styles influence corporate tax avoidance practices. Using regression analysis on data from non-financial companies listed on the Indonesia Stock Exchange (2018-2021), variables such as CEO nationality, financial data, and Effective Tax Rate (ETR) are examined. The study compares tax avoidance practices relative to CEO characteristics. The research reveals a significant negative relationship between Indonesian CEOs and ETR, indicating a propensity for tax avoidance. CEO background, notably nationality, is crucial in shaping strategic decisions regarding tax practices. Robustness tests confirm the relationship's validity, free from observable endogeneity bias. This study focuses on Indonesian CEOs, contributing valuable insights into how executive backgrounds impact corporate tax strategies. It underscores the importance of considering leadership traits in evaluating corporate strategies beyond financial performance.